The Economic Return of the Agricultural Sector to Sudan’s Gross Domestic Product: An Analytical Study (2000-2021) - Norain, Mohmedzain Ahmed Mohmed (Journal of Economic, Administrative and Legal Sciences, 2025)
The study aimed to revead the most important administrative technical and funding problems and obstacles facing the agricultural sector and to show the impact and contributions of the agricultural sector to the gross domestic product and achieiving food security and providing foreign currency. The problem of the study is mainly represented in the deterioration of the agricultural sector, especially the irrigated sector, which has negatively affected its cintribution to the gross domestic product, it can be said that the scarcity of financing and its failure to come at the appropriate times are among the most important obstacles that reduce its contribution to the gross domestic product. The scientific importance stems from the urgent and pressing necessity and relative importance of the agricultural sector, as it contributes to the gross domestic product and achieves food security, and its exports provide a certain amount of foreign currency. The practical importance is the results and recommendatons of the study are of benefit to academics, researchers, and decision makers. The study followed the descriptive analytical method and historical, inductive and statistical method. The study came out with a number of results the most important of wich are: there is a direct relationship with statistical significance between agricultural production and the gross domestic product with the presence of direct relationship with statistical significance between the valume of agricultural exports and the gross domestic product. There is a statistically significant direct relastionship between government spending on the of agricultural sector and the amount of gross domestic product.the study recommended the need for increased attention to the agricultural sector, especially the provision of adequate agricultural financing at appropriate times, and need to follow agricultural and marketing policies that would encourage increased agricultural production and productivity.